Does the development of digital inclusive finance improve the enthusiasm and quality of corporate green technology innovation? - Rui Xu; Dingjun Yao; Ming Zhou (Journal of Innovation & Knowledge (JIK), 2023)
Clarifying the impact of digital inclusive finance (DIF) on green technology innovation is of great practical significance to promote the high-quality development of the green economy in developing countries. In contrast to existing research, this paper conducts a comparative study from the perspectives of innovation enthusiasm and innovation quality and creatively measures the latter based on the annual number of citations of green patents. On this basis, this paper takes Chinese A-share listed companies and the DIF index from 2011 to 2020 as the research objects, finding that the development of DIF has a more significant impact on the quality of green technology innovation than enthusiasm. The characteristics of the external environment, including financial supervision and financing constraints, may have different impacts on the innovation-driven effect of DIF, so the moderating effect model and the threshold model are used to analyze them. In particular, when the government's financial supervision intensity value for DIF is between 0.0024 and 0.0025, financial security can be taken into account, and the high-quality development of green technology can be achieved. In terms of enterprise characteristics, state-owned enterprises and enterprises that do not have a combination of general managers and chairmen can significantly achieve the green innovation-driven effect of DIF. For pollution-intensive enterprises, government supervision is necessary to help them achieve high-quality development of green technology innovation. This study provides policy implications for developing countries around the world to achieve green development by promoting the DIF level.
Keywords: C33; D83; G38; M11; O31; 650; Digital inclusive finance; Fixed effects model; Green technology; Innovation; Threshold effects model